2012
DOI: 10.1111/jam.12043
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into immunological responses against a native recombinant CTB whole-cell Vibrio cholerae vaccine in a rabbit model

Abstract: Aim: The aim of this study was to express and purify the recombinant CTB (rCTB) protein from Vibrio cholerae and investigate the biological and immunological characteristics of purified protein in rabbit animal model and in combination with Iranian inactivated V. cholerae whole cells as a domestic recombinant WC-CTB vaccine. Methods and Results: Expressed 6XHis-tagged rCTB was properly purified, and its identity was confirmed by Western blotting using cholera toxin-specific antibody. Concentration of purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Our previously published data have indicated the pQE- ctx B construct as a highly efficient system to produce rCTB [34] and high affinity binding to GM1 ganglioside [35]. Some advantages of this construct are as follow: i) pQE30 contains the T5 promoter that is recognized by the E. coli host RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…Our previously published data have indicated the pQE- ctx B construct as a highly efficient system to produce rCTB [34] and high affinity binding to GM1 ganglioside [35]. Some advantages of this construct are as follow: i) pQE30 contains the T5 promoter that is recognized by the E. coli host RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rCTB was shown to stimulate the immune response using a rabbit model. 14 Our previous results showed that two different ctxB genotypes were present among V. cholerae isolated from recent outbreaks in Iran. 25 The circulation of inhabitant strains in a region can underline the significance of developing a potent local vaccine composed of our domestic strains with their own cholera toxin antigenic specifications for the control and prevention of cholera outbreaks in this region.…”
Section: 16mentioning
confidence: 93%
“…Recently, we introduced a potent expression system consisting of BL21 (DE3) plus pAE_ctxB construct as an expression vector and have compared it with other expression systems. 14,18 Our previous study demonstrated that expression of rCTB in pAE_ctxB construct is more efficient (15-fold) than pQE_ctxB, and it seems that Lac UV5 in E. coli BL21 (DE3) is more compatible with the former construct. 18 The yield of recombinant CTB produced within this construct in E.coli BL21 (DE3) was about 700 mg l -1…”
Section: 16mentioning
confidence: 99%
See 1 more Smart Citation
“…We should also point out that the adjuvant potential of CTB has also been shown in large animal models, indicating that the adjuvant potential is scalable to higher species (48)(49)(50).…”
Section: Ctb As a Vaccine Adjuvantmentioning
confidence: 89%